2020
DOI: 10.2478/aut-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Importance of Fabric Image Preprocessing for the New Method of Individual Inter-Thread Pores Detection

Abstract: The paper describes the impact and importance of preprocessing methods of fabric image for detection of inter-thread pores (ITP), which is a new method of individual ITP identification. The aim of this experiment is to identify precisely every individual ITP of fabric structure by using optimal preprocessing algorithm for further quantitative, morphometric structural analysis of specialized fabrics (barriers, industrial filters, composites, others) in context of air permeability, flow resistance, UV radiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…is also provides us with a new research idea in image cognition. Next, we will make a cognitive comparative study of color pictures and black and white pictures with preimage processing [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…is also provides us with a new research idea in image cognition. Next, we will make a cognitive comparative study of color pictures and black and white pictures with preimage processing [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…When conducting the image analysis, image processing is extremely important to reduce the loss of data on the structure and size of individual pores. Owczarek described the influence and importance of image pre-treatment methods for interstitial pore (ITP) detection with the aim of accurately identifying each ITP tissue structure using an opti-Fibers 2024, 12, 45 3 of 29 mal pre-treatment algorithm for further quantitative morphometric structural analysis of specialized fabrics [10]. As indicated, the main problem with ITP identification in image analysis was the misclassification of pixels that were close to the edges of the yarn, resulting in image noise among other problems.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the automated determination of porosity has been demonstrated on knitted fabrics 17,18 and weaves. 19,20 Kostajnsek et al 20 give a detailed overview on methods used in the automated determination of porosity. On knitted fabrics, quality control is done by automated imaging in order to determine pilling 21 or do fabric error detection on circular knitting machines.…”
mentioning
confidence: 99%
“…Research on the automated determination of porosity has been demonstrated on knitted fabrics 17,18 and weaves. 19,20 Kostajnsek et al. 20 give a detailed overview on methods used in the automated determination of porosity.…”
mentioning
confidence: 99%